2020
DOI: 10.1534/g3.120.401515
|View full text |Cite
|
Sign up to set email alerts
|

cnd-1/NeuroD1 Functions with the Homeobox Geneceh-5/Vax2 and Hox Geneceh-13/labial To Specify Aspects of RME and DD Neuron Fate inCaenorhabditis elegans

Abstract: Identifying the mechanisms behind neuronal fate specification are key to understanding normal neural development in addition to neurodevelopmental disorders such as autism and schizophrenia. In vivo cell fate specification is difficult to study in vertebrates. However, the nematode Caenorhabditis elegans, with its invariant cell lineage and simple nervous system of 302 neurons, is an ideal organism to explore the earliest stages of neural development. We used a comparative transcriptome approach to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…13C ). For example, miR-43-44, a neuron-specific miRNA, was bound by CND-1/NEUROD1, a motor neuron fate determinant 89 , 90 , while miR-2, a muscle-specific miRNA, was bound by HLH-1/MYF6 and HND-1/PTF1A, two critical TFs that specify body wall muscle fate 91 (Fig. 7B , Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13C ). For example, miR-43-44, a neuron-specific miRNA, was bound by CND-1/NEUROD1, a motor neuron fate determinant 89 , 90 , while miR-2, a muscle-specific miRNA, was bound by HLH-1/MYF6 and HND-1/PTF1A, two critical TFs that specify body wall muscle fate 91 (Fig. 7B , Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To validate whether tissue fate determinants are required for miRNA expression, we focused on known determinants of five major tissue types: CND-1 (a subset of neurons) 89 , 90 ; PHA-4 (pharynx) 74 , 92 ; ELT-1 (skin) 93 ; HLH-1, HND-1, and UNC-120 (muscle) 91 ; and ELT-2 (intestine) 94 . We perturbed these TFs using loss-of-function alleles or RNAi and quantified in nine experiment sets the cellular expression of tissue-specific miRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…The role of the anterior Hox gene ceh-13 during C. elegans neuronal terminal differentiation is largely elusive, partly due to the early larval lethality of ceh-13 mutants (Brunschwig et al, 1999). A recent study suggested ceh-13 controls terminal identity features of GABAergic motor neurons (DD1, DD2) located in the anterior ganglion, but the underlying mechanisms remain unknown (Aquino-Nunez et al, 2020).…”
Section: Hox Genes Control Terminal Identity Features Of Ventral Nerv...mentioning
confidence: 99%
“…Out of all the conserved proteins, none of the family member of NeuroD have been incorporated into the sea urchin neuronal GRN. NeuroD (NeuroD1, NeuroD2, and NeuroD6) TFs are members of the neuronal lineage basic helix‐loop‐helix family that regulate the transition from neuronal differentiation to maturation in vertebrate/invertebrate systems (Amador‐Arjona et al., 2015; Aquino‐Nunez et al., 2020; Cho & Tsai, 2004; Huang et al., 2011; Liu et al., 2011; Masoudi et al., 2018; Matsuda et al., 2019; Pataskar et al., 2016). NeuroD1, specifically, is expressed early in mammalian embryos to regulate neuronal development, suggesting that it is a good candidate to be incorporated into the sea urchin neuronal GRN (Matsuda et al., 2019; Pataskar et al., 2016; Tutukova, Tarabykin, & Hernandez‐Miranda, 2021).…”
Section: Introductionmentioning
confidence: 99%